The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18632/oncotarget.13505
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of three-dimensional echocardiographic right ventricular ejection fraction in patients with pulmonary arterial hypertension

Abstract: BackgroundRight ventricular (RV) function is an independent predictor of clinical outcomes in patients with pulmonary arterial hypertension (PAH). However, it remains controversial which RV parameter should be measured as an appropriate index for the treatment of PAH. The aim of this study was to identify the most useful parameter that correlates with hemodynamics and predicts clinical outcomes in PAH.ResultsMost of the clinical and echocardiographic RV parameters were significantly correlated with pulmonary v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…In primary pulmonary hypertension patients, a close relationship can be observed between pulmonary vascular resistance and various RV functional parameters. 27 Moreover, these patients show maintained longitudinal RV shortening for a long time and the loss of radial function is suggested to be an early marker of the disease. 28,29 These findings are not concordant with what is seen in HTX patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In primary pulmonary hypertension patients, a close relationship can be observed between pulmonary vascular resistance and various RV functional parameters. 27 Moreover, these patients show maintained longitudinal RV shortening for a long time and the loss of radial function is suggested to be an early marker of the disease. 28,29 These findings are not concordant with what is seen in HTX patients.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, we should be cautious highlighting only pulmonary pressures regarding RV functional shift on a long‐term follow‐up. In primary pulmonary hypertension patients, a close relationship can be observed between pulmonary vascular resistance and various RV functional parameters . Moreover, these patients show maintained longitudinal RV shortening for a long time and the loss of radial function is suggested to be an early marker of the disease .…”
Section: Discussionmentioning
confidence: 99%
“…Normative data are available for this methodology and the normal right ventricular ejection fraction using these methods is !45% [8]. Recent data reported the three-dimensional right ventricular ejection fraction had a stronger correlation with directly mean pulmonary artery pressure than traditional measured of right ventricular systolic function [14].…”
Section: Right Ventricular Systolic Functionmentioning
confidence: 99%
“…Newer echocardiographic techniques have also been shown to predict poor outcome in pulmonary hypertension including reduced right ventricular longitudinal strain [15][16][17][18][19], poor global right ventricular area strain [20] and reduced three-dimensional right ventricular ejection fraction or greater end-systolic indexed volumes [14,20,47,48].…”
Section: Prognostic Utility Of Echocardiography In Pulmonary Hypertenmentioning
confidence: 99%
“…This may suggest that RVEF is significantly correlated with PH. Murata et al [1] reported that RVEF measured by 3D echo could help to noninvasively predict the clinical outcomes of PH. Thus, 3D echo data might be useful for evaluating patients' cardiac condition and choosing treatment.…”
mentioning
confidence: 99%